BALANCING INVESTOR PROTECTION WITH A STATE’S REGULATORY AUTONOMY IN THE AMENDED SADC FIP - Mmiselo Freedom Qumba (Obiter, 2021)
This article focuses on the 2016 Amended Annex 1 to the Southern African Development Community (SADC) Finance and Investment Protocol (FIP) (the Amended Annex), which entered into force on 22 August 2017. It aims at a comprehensive assessment of the adequacy of the Amended Annex in balancing investor protection with SADC member states’ quest for domestic policy space in the content of the treaty provisions. Prior to the amendment, the 2006 SADC FIP contained clauses that were considered challenging in the old international investment agreements (IIAs) – such as broad definitions of “investor” and “investment”, provision for international arbitration as a recourse, and according foreign investors fair and equitable treatment (FET) and most favoured nation (MFN) treatment. The challenges associated with bilateral investment treaties (BITs) (especially investor-state dispute settlement (ISDS) mechanisms, restrictions on sovereign policy space and regulatory autonomy) necessitated a review by the SADC member states of the 2006 SADC FIP. The purpose of this article is to reflect on the implications of the 2016 Amended Annex 1 to the SADC FIP with a view to finding a balance between protection enjoyed by investors and the host states’ right to regulate. The article adopts a comparative international law approach, which is useful in order better to understand a SADC member country’s approach to foreign investment protection.